A Cross-Linguistic Investigation of the Effect of Raters' Accent Familiarity on Speaking Assessment. Issue 1 (2nd January 2016) - Huang, Becky; Alegre, Analucia; Eisenberg, Ann
ABSTRACT: The project aimed to examine the effect of raters' familiarity with accents on their judgments of non-native speech. Participants included three groups of raters who were either from Spanish Heritage, Spanish Non-Heritage, or Chinese Heritage backgrounds ( n = 16 in each group) using Winke & Gass's (2013) definition of a heritage learner as being someone who reports cultural or ethnic ties and has family members who are native speakers of that heritage language. Using a 1–7 Likert-type scale, all participants evaluated the "overall English proficiency" and "foreign accents" of 28 speech samples selected from Educational Testing Service's TOEFL iBT public data set. Approximately half of the speech samples were from speakers with a Spanish language background, and the other half were from speakers with a Chinese language background and were matched on English language proficiency. Results revealed that familiarity with a particular accent facilitated the identification of that accent. Although the three rater groups did not differ reliably in the ratings assigned to the speakers, the majority self-reported that their accent familiarity affected their evaluations and possibly made them more lenient toward speakers with familiar accents. Furthermore, all rater groups assigned higher ratings to Spanish speakers than to Chinese speakers.